Depiction of Vayu - Temples of India Project Team (Jio Institute, 2024)
The opposite side of the niche, of the kakshasana (seat back) of the Undeshwar Temple, portraying Varuna features Vayu. Vayu is depicted as a tall, smiling figure with four arms, shown standing. He holds a staff in his upper hands, while a kamandalu (water pot) and a gesture of varadaksha (of blessing) are depicted in his lower hands. At the bottom of the niche, Vayu's vehicle, the antelope, is depicted in motion.